An Approach to Estimate the Parameters of Aiba-Edward Growth Model Using the Growth of Escherichia Coli - Gogoi, Udoy Narayan; Saikia, Pallabi; Mahanta, Dimpal Jyoti (Communications in Mathematics and Applications, 2023)
In microbial growth kinetics mathematical models are used to correlate the growth rate to the concentration of the limiting substrate with the parameters. Aiba-Edward model is one of the widely used models to describe microbial growth kinetics. In this study, four new methods are introduced to estimate the model’s parameter using a standard bacterial growth data of Escherichia Coli. The performance of the introduced methods are analyzed by using a standard selection criterion. In this study, it has been observed that the newly introduced methods are performed well and estimated parameters are biologically significant.